Pengaruh Karakteristik Rumah Tangga, Keragaman Makanan, Lingkungan Hidup terhadap Status Gizi Balita - Fitria Nur Rahmawati; Tri Mulyaningsih; Akhmad Daerobi (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
The household or family is a place for children to maximize their growth and development and fulfilltheir nutrition, to create high-quality human resources and to drive the country’s economic growth for thefuture. This study aims to examine factors of household socioeconomic characteristics, dietary diversity, andthe environment and their effects on the nutritional status of children under five in Indonesia. This study usescross-sectional design and uses secondary data from Indonesia Family Live Survey (IFLS) wave 5 (IFLS5). IFLSis a longitudinal survey of a random sample of 83% of the population in Indonesia in 1993. The sample in thisstudy was children aged 0-60 months (toddlers), totaling 4,670 children under five. The research method is touse a multinomial logistic regression model. The results showed that the nutritional status of children under fiveyears old was affected by family income, mother’s education, the gender of children under five, residential areas,access to drinking water and good sanitation. The conclusion is that the mother’s education has a significantinfluence on the three nutritional status of children under five, namely wasted, severely wasted, and overweight.